Museum and Gallery of Contemporary Art Medan (Contemporary Architecture) - Imam Faisal Pane; Rahmita Dewi Lubis (International Journal of Architecture and Urbanism, 2017)
The Museum is a place to see showpieces as art, artifacts, and other cultural relics. The purpose of the museum is not only for education but also as entertainment. This design takes the case study of a contemporary art museum. This museum has a gallery, which function is to sell and auction the contemporary art. This Museum and Gallery designed with contemporary architecture style, suitable for the main function of the building which is museum and gallery of contemporary art. The museum and gallery will also help to develop the tourism in Medan and to be an education facility to the public. There are few steps made in the process of completing the design; the first one is by collecting data from the literature, books, journal, magazine, the internet, survey, and interview. And from the data collected, the design for Museum and Gallery of Contemporary Art will be produced.